2008
DOI: 10.1108/09593840810919671
|View full text |Cite
|
Sign up to set email alerts
|

Do virtual communities matter for the social support of patients?

Abstract: Purpose-The purpose of this paper is to explore whether online communities meet their potential of providing environments in which social relationships can be readily established to help patients cope with their disease through social support. The paper aims to develop and test a model to examine antecedents of the formation of virtual relationships of cancer patients within virtual communities (VCs) as well as their effects in the form of social assistance. Design/methodology/research-Data were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…Empirical virtual community studies contend, counter to early computer mediated communication findings [45]- [47], that strong relationships can be forged online, and often these relationships extend beyond the Internet. Further, cancer patients have been shown to benefit from supportive virtual relationships with fellow cancer patients and cancer survivors [24], with whom they can share practical and experiential knowledge [22], [43], [44]. Eysenbach, Powell, Englesakis, Rizo and Stern et al, [38] found that online relationships not only provide an outlet for getting support and information, they actually positively impact patients' long-term prognosis [24].…”
Section: Virtual Community Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Empirical virtual community studies contend, counter to early computer mediated communication findings [45]- [47], that strong relationships can be forged online, and often these relationships extend beyond the Internet. Further, cancer patients have been shown to benefit from supportive virtual relationships with fellow cancer patients and cancer survivors [24], with whom they can share practical and experiential knowledge [22], [43], [44]. Eysenbach, Powell, Englesakis, Rizo and Stern et al, [38] found that online relationships not only provide an outlet for getting support and information, they actually positively impact patients' long-term prognosis [24].…”
Section: Virtual Community Literaturementioning
confidence: 99%
“…Early definitions of virtual communities emphasized computer mediation of communication, but modern definitions are more comprehensive and highlight the importance of social connections [23]. Virtual communities are essentially 'social structures' made up of a network of virtual relationships where the first contact takes place online, and are most often formed around a topic of interest [23], [24]. Rather than geographic boundaries, virtual communities are defined by shared interests and selfidentification [23], [38].…”
Section: Virtual Community Literaturementioning
confidence: 99%
See 3 more Smart Citations